Ecologia trófica da comunidade de peixes do reservatório de Cachoeira Dourada, rio Paranaíba, Bacia do Alto Rio Paraná, Brasil - Velludo, Marcela Roquetti (2011)
The knowledge of the fish s diet and species abundance of a particular community allows us to identify the community s different trophic categories, as well as to infer about its structure. This knowledge may also permit to evaluate the degree of importance of trophic levels and to understand the interrelationships among the components of that community. In order to generate data for a better understanding of the relationships between the ichthyofauna components and other aquatic organisms in the community, this study aimed to characterize the trophic structure of the fish community of the Cachoeira Dourada reservoir - MG/GO, Upper Parana River basin (18° 30' 11.47"S, 49° 29' 18.78"W). The fish sampling occurred monthly from February 2007 to January 2008 and the fishes were captured using gill nets of 2 to 6.5 inches between adjacent knots placed at three sampling points of the reservoir. The biometric analyses was performed by the gauging of the total and standard length and total weight of the collected specimens. The fish stomachs were removed, weighed and fixed in 4% formaldehyde for further analysis in stereomicroscope. The data obtained during the stomach contents analysis was quantified though the Alimentary Index of Kawakami and Vazzoler, which combines the frequency of occurrence and volume of the alimentary items. The description of the species diet allowed the identification of six feeding guilds: (1) Iliophagous, (2) Carnivores-insectivores, (3) Carnivores-piscivores, (4) herbivores, (5) Omnivores, (6) Invertivores. The dietary overlap trophic web built showed interspecific interactions with 20% connectance. Eleven sub-groups or clicks were observed. The iliophagous sub-group showed no interactions with other species guilds. The bipartite network showed the generality of the food items intake of Pimelodus maculatus, the most abundant species in gill nets catches. The prey relative biomass appeared to be larger than that of the predators, this factor may be responsible for maintaining the large amount of piscivorous species found in the community. The ecosystem analyses describe and evaluate the functioning of biological systems considering productivity, interaction between communities and their functional processes. The knowledge of trophic ecology and key species connectivity indicates the paths through which the greater part of the system energy flows. This can help to identify regulatory elements of the community s structure and functioning, since it summarizes the dynamics of environmental energy transfer.